PRAKTEK PERNIKAHAN DI BAWAH UMUR Di Kenagarian Bawan Kecamatan Ampek Nagari Kabupaten Agam Sumatera Barat - Zulkhairi, Zulkhairi; Manan, Abdul (Mitsaqan Ghalizan, 2021)
The title of this research is The Practice of Underage Marriage in Kenagarian Bawan, Ampek Nagari District, Agam Regency, West Sumatera. The background of this research problem is based on Article 7 paragraph 1 of Law No. 1 of 1974 concerning Marriage which states that "marriage is only permitted if the male party has reached the age of 19 years and the female has reached the age of 16 years, while in Nagari Bawas, Ampek Nagari Sub-district, Agam Regency, many people ignore this provision. The purpose of this study was to see the form of implementation and the factors causing the practice of underage marriage in Kenagarian Bawan, as well as the actions taken by religious leaders, traditional leaders and KUA officials. This type of research is empirical legal research or legal sociology. That is an approach by looking at a legal reality in society. The sociology of law approach is an approach used to look at legal aspects in social interactions in society. Data taken from interviews with the Head of the Office of Religious Affairs (KUA) and parties involved in the practice of underage marriage. The results showed that the practice of underage marriage in Kenagarian Bawan was only carried out in front of the local Tuanku, not in front of the Marriage Registrar, in the sense that this marriage was an illegal/unofficial marriage according to the Positive Law of Indonesia. There are three contributing factors, namely: pregnancy factors, educational factors and economic factors. Actions taken by religious leaders, traditional leaders and KUA officials are in the form of socialization and counseling to the community.